DŮM NA HRANĚ - Valašské Meziříčí, ulice Sokolská - Ehlová, Veronika (Vysoké učení technické v Brně. Fakulta architektury)
Cílem bakalářské práce je návrh polyfunkčního domu v centru Valašského Meziříčí. Navržený projekt respektuje historii a urbanistickou typologii místa. Koncept vychází z motivu hradby převedené do současného pojetí, vytvoření klidného bydlení a oživení okolí

The objective of bachelor thesis is a design of polyfunctional house in the center of Valašské Meziříčí. The project respects the history and typology of urban space. The concept is based on the theme of walls converted into the current conception, a quiet housing and neighborhood revitalization.
HOUSE ON THE EDGE – Valašské Meziříčí, Sokolská Street
Keywords: Valašské Meziříčí; polyfunkční dům; dům na hraně; bydlení; fitnesscentrum; slunolamy; Valašské Meziříčí; polyfunctional building; a house on the edge living; fitness center; sunshades